(untitled) (Biological Sciences - PJSIR, 2020)
The ’1Scos1tics or LiCI and NaCl solutions for different concentrations in aqueous butanol (0-7°0) mi,..lures al ,·arious lcmpcralurcs were measured The viscosity dala was intcrprcled in terms of ion-solrnnt interactions. A regular mcrcmcm m the v1scosit1cs "11h the mcn:asing conccmrations of sail as well as increasing in percent composition of aqueous butanol mixtures is observed The ,alues of A & B coeOicients or Jones-Dole equation have been dctem1ined gr:1ph1call) . lt 3S found that A & B coellic1cnts ,ary with concenlrat1on of LiCJ and NaCl as 1th the composition of bulllnol mixtun:s and temperatures. The positi, c values of B- coeflicicnt decreased with rise in l.:rnpcralurc led to the conclusion lhat NaCl and LiCI in aqueous butanol mixtures bcha,·c as structure maker whereas. m aqueous medium NaCl ttnd LiCI showing negative values of B-eoetlicient behave as structure breakers. An attempt has also been made to determine the acti,·ation energy ( E,) as a function of conccntr,1tion of l.iCI and NaCl in aqucous-butanol mi’ltures. It sho s that actirntion energy is int1ucnccd b the conccnlr:ition of salts and percent composition of soh·enls.